Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada Madira Skin & Beauty Care - Nicken Amelania Widyaning Putri; Beny Mahyudi Saputra; Nur Hidayati (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The purpose of this study to determine the effect of motivation and work discipline on employee performance at Madira Skin & Beauty Care. This research applies quantitative approach. Sampling techniques apply non-probability sampling which means that the sample used is all employees of Madira Skin & Beauty Care. Data obtained from observations, interviews, and questionnaires. Using validity test analysis techniques, reliability test, classical assumption test, multiple linear regression test, coefficient of determination test, Partial Test (t), and simultaneous test (f). The results of data analysis showed that motivation has a significant effect partially on employee performance, work discipline does not have a significant effect partially on employee performance, motivation and work discipline have a significant effect simultaneously on employee performance. This can be seen from the results of correlation analysis, namely: the value of R square 0.525 or 52.5% and the remaining 47.5% are influenced by other variables that are not included in the study.